2015
DOI: 10.1021/ef5019862
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Alkalis on Interfacial Tensions of Surfactant/Polymer Solutions against Hydrocarbons

Abstract: The dynamic interfacial tensions (IFTs) of enhanced oil recovery (EOR) surfactant/polymer/organic alkali systems against a homologous series of alkanes have been investigated by a spinning drop interfacial tensiometer. Two organic alkalis with different molecular sizes, ethanolamine (EA) and diethanolamine (DEA), two surfactants with high interfacial activity, heavy alkyl benzenesulfonate (HABS) and petroleum sulfonate (SLPS), and two kinds of polymers, partly hydrolyzed polyacrylamide (HPAM) and hydrophobical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The IFT trend obtained in the present study for hydrocarbon−brine system is also analogous to the hydrocarbon−brine system that contains petroleum sulfonate. 47 It was observed that the relative decrease in IFT with respect to 0 ppm salt concentration for n-heptane−brine system is more than that of toluene−brine system for mixed monovalent and divalent brine system. The impact of composition of salt on the IFT of n-heptane−brine system and toluene−brine system was the same and of the order B9 > B8 > B7.…”
Section: Resultsmentioning
confidence: 99%
“…The IFT trend obtained in the present study for hydrocarbon−brine system is also analogous to the hydrocarbon−brine system that contains petroleum sulfonate. 47 It was observed that the relative decrease in IFT with respect to 0 ppm salt concentration for n-heptane−brine system is more than that of toluene−brine system for mixed monovalent and divalent brine system. The impact of composition of salt on the IFT of n-heptane−brine system and toluene−brine system was the same and of the order B9 > B8 > B7.…”
Section: Resultsmentioning
confidence: 99%
“…The comparison of Figure 1a,d showed that that the concentration of NO 3 − -N is the highest, while the removal rate of NH 4 + -N is the lowest, in the presence of SDS. It was found that the activated sludge in SBRs was affected not only by surfactants [23,33], but also by high salinity [20,26,34]. High salinity has a strong inhibition effect on sludge activity [18], but the interaction between surfactant and salt weakens the inhibition of salt on the activated sludge.…”
Section: Removal Performance Analysismentioning
confidence: 99%
“…When the dosage of SDBS is 0.02 g/g dry sludge, the activity of amylase and proteinase is the best [25]. Moreover, the interaction between salt and surfactant can affect the interfacial tension of the surfactant [26], thus affecting the sludge activity. However, the role of surfactant on the activated sludge system is still unclear, especially under the high salt conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the concentration of ABS itself, temperature, concentration of electrolytes in solution, [8][9][10][11] organic bases, 12,13 and so on can affect the reduction of IFT. Specically, the ABS structure is the most complex factor.…”
Section: Introductionmentioning
confidence: 99%